Radikalizacija in religijski ekstremizem v luči svobode religije in prepričanja - Andrejč, Gorazd (Časopis za kritiko znanosti, 2020)
The concept of radicalization related to religion, which is used in official documents and affects the official discourse, contains the idea that the end point of radicalization is dangerous extremism or terrorism. Accordingly, radicalized individuals are viewed as posing a serious threat to society. When a radicalized individual is detected, the proposed course of action is to monitor them through state institutions in an attempt to prevent further radicalization or de-radicalize them. This approach provides moral and often legal justification for the encroachment on certain rights and freedoms of individuals that the state labels as radical. The discussion usually revolves around the rights to privacy, freedom of speech, and citizenship. The author takes a different approach and instead discusses the issue of radicalization through the lens of the right of freedom of religion and belief. In democratic societies, this a crucial and basic freedom; in a certain sense, it is even unlimited as beliefs are impossible to control and should not be controlled. Nevertheless, the state can and should limit practices and acts that can be connected to certain beliefs, religious or otherwise. Given this context, the author presents and analyzes the case of Islamist extremist Anjem Choudary.
Keywords: belief; Choudary, Anjem; freedom of religion; locution; lokucija; prepričanja; radicalization; radikalizacija; religija; religions; religious extremism; svoboda religije; verski ekstremizem